Millimeter Wave Radar: Hardware and Signal Processing - Waldschmidt, Christian; Bonfert, Christina; Grebner, Timo (Springer Nature, 2025)
This open access book covers millimeter-wave radar technology as used today in advanced applications such as automated driving and industrial sensor technology. Each topic is discussed from a comprehensive systems perspective, thoroughly addressing both signal processing and hardware aspects, along with their interconnections. After a solid introduction to the basics and applications of radar sensors, the focus shifts to the fundamental operating principles of these sensors. Separate chapters then cover signal processing and hardware concepts in detail. Finally, the book concludes with an in-depth discussion of specialized radar techniques, including imaging radar.